STRATEGI PENGELOLAAN ORGANISASI PENDIDIKAN MELALUI SISTEM PENGELOLAAN KEBIJAKAN KEUNGGULAN KOMPETITI(Untuk Peningkatan Kualitas SDM Pengelola Pendidikan) - Sahrul Tanjung (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
It is time for the community to start to improve themselves to make changes to the strategy for managing educational institutions that are business-oriented, this is because the Indonesian government has financial limitations in investing in education, so the management of national education is less effective. In an effort to overcome such situations, there is a need for discourse the social education management system shifted to an interprise management system that was oriented towards competitive advantage by developing business principles that were centered on the satisfaction of educational service users. Of course, the discourse on the policy strategy for managing competitive advantage is a big challenge for every educational institution in